Hydrogen Gas Blending in Gasoline GDI Engines: Combustion Analysis and Emission Control - Onawale O. Tairu; Olusegun O. Ajide; Olawale S. Ismail; Olanrewaju M. Oyewola (Thermo, 2025)
This study investigates the effects of varying hydrogen percentages in fuel blends on combustion dynamics, engine performance, and emissions. Experimental data and analytical equations were used to evaluate combustion parameters such as equivalent lambda, in-cylinder pressure, heat release rate, and ignition timing. The findings demonstrate that hydrogen blending enhances combustion stability, shortens ignition delay, and shifts peak heat release to be closer to the top dead center (TDC). These changes improve thermal efficiency and reduce cycle-to-cycle variation. Hydrogen blending also significantly lowers carbon dioxide (CO2) and hydrocarbon (HC) emissions, particularly at higher blend levels (H0–H5), while lower blends increase nitrogen oxides (NOx) emissions and risk pre-ignition due to advanced start of combustion (SOC). Engine performance improved with an average hydrogen energy contribution of 12% under a constant load. However, the optimal hydrogen blending range is crucial to balancing efficiency gains and emission reductions. These results underline the potential of hydrogen as a cleaner additive fuel and the importance of optimizing blend ratios to harness its benefits effectively.